2002
DOI: 10.1159/000063316
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Cytomegalovirus-Associated Interstitial Nephritis in a Kidney Transplant

Abstract: Cytomegalovirus is the most important viral infection in kidney transplants, but rarely affects the allograft after the sixth month posttransplantation. We present a patient who developed renal failure eighteen months posttransplant; a kidney biopsy showed cytomegalovirus inclusions, acute tubular necrosis and mild interstitial nephritis. After intravenous ganciclovir, renal function transiently improved. Cytomegalovirus pp65 antigen was weekly reported as negative. One month later another biopsy was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…We observed that CMV antigenemia is associated with ATI in early protocol biopsies. So far, similar observations have only been published in one single case report that showed viral inclusions and tubulointerstitial nephritis in the renal allograft (22).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We observed that CMV antigenemia is associated with ATI in early protocol biopsies. So far, similar observations have only been published in one single case report that showed viral inclusions and tubulointerstitial nephritis in the renal allograft (22).…”
Section: Discussionsupporting
confidence: 65%
“…So far, similar observations have only been published in one single case report that showed viral inclusions and tubulointerstitial nephritis in the renal allograft (22). So far, similar observations have only been published in one single case report that showed viral inclusions and tubulointerstitial nephritis in the renal allograft (22).…”
Section: Discussionmentioning
confidence: 60%